Three-dimensional model of Dictyodora Weiss: new ichnotaxonomical perspectives - Gutiérrez, Carolina (2024)
Dictyodora is a complex three-dimensional Paleozoic marine ichnogenus that has been studied for more than a century. However, several problems for the diagnostic features as valid ichnotaxobases remain debatable at an ichnospecific level. Dictyodora is defined on the basis of two parts: an almost horizontal structure named lower margin (here named basal burrow) and a thin medial structure known as the spreite (Fig. 1). The latter is disposed angularly to the basal burrow with a variable inclination (e.g., 40 to 90°). The spreite is usually preserved as hypichnial epireliefs or epichnial hyporeliefs and is the most frequent feature preserved on a bedding plane. The morphological variations of the spreite have been used as a diagnostic characteristic at ichnospecific level [1,2]. Numerous specimens analyzed from the middle Paleozoic (Silurian-Devonian) of Argentina (central-western Gondwana) recorded morphological transitions between ichnospecies, never reported before in the literature [3,4,5,6]. These records allow to point out several problems: most ichnospecies have an unclear diagnosis or vague descriptions; some diagnostic features are shared for more than one ichnospecies; and morphological intergradations assignable to different ichnospecies along a same specimen are observed. Moreover, intergradations between ichnospecies have been documented since the ichnogenus creation but never mentioned as such [7,8].In this work, new examples of intergradation involving also other ichnospecies of the ichnogenus Dictyodora are presented and studied in detail (Table 1). The specimens are recorded in a middle Paleozoic unit of Argentina. Those specimens reflect intergradation between most of Dictyodora’s ichnospecies. Some exceptions are the intergradation of Dictyodora tenuis (M’ Coy) with Dictyodora liebeana (Geinitz), Dictyodora silurica Yang and Hu but also with D. zimmermanni Hundt. Notably, D. silurica is the only ichnospecies without intergradation with any another ichnospecies.For instance, one of the specimens (IANIGLA-Icn 92) contains morphological features that show the spreite at different bedding planes. One of them is close to the basal burrow (level 1) and the other is more distant to the basal burrow (level 2; Fig. 2). The three-dimensional reconstruction model documents variations in a vertical axis of the same structure between both levels. This model was obtained using photogrammetry techniques. The obtained images of the sample were processed using Meshroom Version 2021.1.0, and the open-source software Blender Version 3.3.1 was utilized for the interpretation and modeling of the final render. At level 1, the spreite presents a regular meandering trajectory with rounded or angular bends (archs), the latter being the most abundant, allowing this form to be assigned to Dictyodora atuelica Pazos et al. It continues laterally with regular meanders showing rounded archs assignable to Dictyodora scotica (M’ Coy) and ends in smaller and irregular meanders characteristic of D. tenuis. Conversely, at level 2 the spreite presents a regular meandering pattern with predominantly rounded archs, assignable to D. scotica. The meanders continue with others showing angular archs, assignable to D. atuelica. Interestingly, it ends with regular meanders with rounded archs, typical of D. scotica. In conclusion intergradations are observed in both levels of the same specimen but involving different ichnospecies. The numerous types and cases of intergradation observed in the material analyzed in this work but also in the revision of the literature regarding to intergradation between ichnospecies belonging to Dictyodora allow to discuss diagnostic ichnotaxobases at ichnospecific level. The vertical variations (between levels 1 and 2) in the morphology of the spreite are not related to changes in the ethology of the producer. This suggests that most of the valid ichnospecies are the result of splitting in different ichnospecies the record of morphological variations, which may not be related to ethological changes. This invites to revise the ichnotaxobases used for differentiation of Dictyodora ichnospecies.